The Ketogenic Diet for the Treatment of Mood Disorders in Comorbidity With Epilepsy in Children and Adolescents - Operto, Francesca F.; Matricardi, Sara; Pastorino, Grazia Maria Giovanna; Verrotti, Alberto; Coppola, Giangennaro (Frontiers in Pharmacology, 2020)
The ketogenic diet, used for over a century as an alternative therapy for the control of drug-resistant seizures in both children and adults, has recently drawn increasing interest in various neurological or psychiatric disorders other than epilepsy. In particular, there are a few preliminary studies in mood and neurodevelopmental disorders such as anxiety, depression and autism spectrum disorders. Mood disorders in comorbidity with epilepsy are commonly seen in adolescents and young adults both at the onset and during the course of the epileptic disorder. The rationale for the use of the ketogenic diet is based on the potential mood stabilizing effects through level modifications of metabolites such as dopamine and serotonin and the regulation of GABA/glutamatergic neurotransmission, mitochondrial function and oxidative stress. In this review, epilepsies with a higher risk of mood disorders in adolescents will be considered. A brief overview of the various types of ketogenic diet that can currently be offered to young patients in order to improve palatability and compliance with the diet, is also included. The efficacy and tolerability of the ketogenic diet options for the treatment of mood disorders, with or without drug therapy including mood stabilizers and antidepressant drugs, are as well discussed.